(untitled) (The International Journal for Scientific Research, 2025)
The study was titled "Islamic preaching and its impact on social life in the Kingdom of Bagirmi." The study aims to revive the Islamic heritage, clarify the ideas that mar the history of the Islamic call, and the role played by the Islamic call in forming, protecting and developing the Islamic Kingdom of Bagirmi from a social standpoint, and the apparent status of the Islamic religion in it. The study asked questions to try to answer: - Did Islam enter the Lake Chad Basin region in general and the Kingdom of Bagirmi in particular early ? And helped form the Islamic Kingdom of Bagirmi ? - What is the impact of the Islamic call on the Kingdom of Bagirmi ? - Does the Kingdom of Bagirmi benefit from the Islamic call from a social standpoint ? The study followed: the historical, descriptive and analytical approach. The study consisted of two requirements as follows : - The first requirement: The entry of Islam into the Lake Chad Basin region and its impact on the Kingdom of Bagirmi, dealing with the geographical and astronomical location of the Kingdom of Bagirmi, the area of the Kingdom of Bagirmi, the emergence of the Kingdom of Bagirmi, and the entry of Islam into the Lake Chad Basin region and its impact on the Kingdom of Bagirmi. - The second requirement: The impact of the Islamic call on social life in the Bagirmi Kingdom, and the social heritage in the Bagirmi Kingdom, residents of the Bagirmi region, Bagirmi’s word, song, religious duties (tattoos), decorative tools. - The study then concluded with findings and recommendations.